Impact of clinical risk factor profile vs. atrial fibrillation phenotype on outcome after pulmonary vein isolation. (14th October 2021) - Wittmer, S; Chollet, L; Baldinger, S; Servatius, H; Seiler, J; Madaffari, A; Kueffer, T; Muehl, A; Asatryan, B; Lam, A; Noti, F; Haeberlin, A; et al.
Abstract: Aims: Catheter ablation for atrial fibrillation (AF) is increasingly performed. Both clinical risk factors as well as the AF phenotype have been shown to influence ablation outcomes. The inter-relationship of the two however is incompletely understood. Methods: In a retrospective analysis of a prospective registry of patients undergoing a first pulmonary vein isolation, the association of 8 predefined clinical risk factors (age >70 years, female gender, hypertension, BMI >30 kg/m 2, coronary artery disease, heart failure, chronic kidney disease (CKD; eGFR<60ml/min/1.73m 2 ) and diabetes mellitus) and the AF phenotype (paroxysmal vs. persistent AF) were assessed as well as their impact on AF recurrence during follow-up. Results: Overall, 715 patients were enrolled (median age 63 years, 27% females, 69% paroxysmal AF). The prevalence of obesity, hypertension, heart failure and CKD was significantly higher in persistent AF, while female gender was more prevalent in paroxysmal AF. After 2 years of follow-up, overall freedom from recurrence was 46%, and was higher in paroxysmal AF compared to persistent AF (54.1% vs. 29.1%, p<0.001). Of the clinical risk factors, obesity (p=0.02), CKD (p=0.01) and heart failure (p=0.01) were significantly associated with lower arrhythmia-free survival, and there was a trend for hypertension and coronary artery disease (both p<0.2). A risk score composed of those 5 factors was associated with recurrences in patients with paroxysmal AF (p=0.04, Figure 1), but not in those with persistent AF (p=0.85, Figure 2). Conclusion: Clinical risk factors predict outcome after pulmonary vein isolation in patients with paroxysmal, but not persistent AF. This is likely due to a strong association of those risk factors with the occurrence of persistent AF. Funding Acknowledgement: Type of funding sources: None.